Macrophages release neuraminidase and cleaved calreticulin for programmed cell removal - Allison Banuelos; Michelle Baez; Allison Zhang; Leyla Yılmaz; William Kasberg; Regan Volk; Nardin Georgeos; Elle Koren-Sedova; Uyen Le; Andrew T. Burden; Kristopher D. Marjon; Jennifer Lippincott-Schwartz; et al. (Proceedings of the National Academy of Sciences, 2025)
Calreticulin (CALR) is primarily an endoplasmic reticulum chaperone protein that also plays a key role in facilitating programmed cell removal (PrCR) by acting as an “eat-me” signal for macrophages, directing their recognition and engulfment of dying, diseased, or unwanted cells. Recent findings have demonstrated that macrophages can transfer their own CALR onto exposed asialoglycans on target cells, marking them for PrCR. Despite the critical role CALR plays in this process, the molecular mechanisms behind its secretion by macrophages and the formation of binding sites on target cells remain unclear. Our findings show that CALR undergoes C-terminal cleavage upon secretion, producing a truncated form that functions as the active eat-me signal detectable on target cells. We identify cathepsins as potential proteases involved in this cleavage process. Furthermore, we demonstrate that macrophages release neuraminidases, which modify the surface of target cells and facilitate CALR binding. These insights reveal a coordinated mechanism through which lipopolysaccharide (LPS)-activated macrophages regulate CALR cleavage and neuraminidase activity to mark target cells for PrCR. How they recognize the cells to be targeted remains unknown.